Estrogen as a Neuroprotectant in Both Sexes: Stories From the Bird Brain - Saldanha, Colin J. (Frontiers in Neurology, 2020)
Estrogens like estradiol (E2) are potent effectors of neural structure and function via peripheral and central synthesis. In the zebra finch (Taeniopygia guttata), neural E2 synthesis is among the highest reported in homeotherms due to the abundant constitutive expression of aromatase (E-synthase) in discrete neuronal pools across the forebrain. Following penetrating or concussive trauma, E2 synthesis increases even further via the induced expression of aromatase in reactive astrocytes around the site of damage. Injury-associated astrocytic aromatization occurs in the brains of both sexes regardless of the site of injury and can remain elevated for weeks following trauma. Interestingly, penetrating injury induces astrocytic aromatase more rapidly in females compared to males, but this sex-difference is not detectable 24hr post-trauma. Indeed, unilateral penetrating injury can increase E2 content four-fold relative to the contralateral uninjured hemisphere suggesting that glial aromatization may be a powerful source of neural E2 available to circuits. Glial aromatization is neuroprotective as inhibition of injury-induced aromatase increases neuroinflammation, gliosis, necrosis, apoptosis and infarct size. These effects are ameliorated upon replacement with E2 suggesting that the songbird may have evolved a rapidly responsive neurosteroidogenic system to protect vulnerable brain circuits. The precise signals that induce aromatase expression in astrocytes include elements of the inflammatory cascade and underscore the sentinel role of the innate immune system as a crucial effector of trauma-associated E2 provision in the vertebrate brain. This review will describe the inductive signals of astroglial aromatase and the neuroprotective role for glial E2 synthesis in the adult songbird brains of both sexes.